Influence of Healthscapes and Mimetic Desire on Birthing Place Choice Mediated by Perceived Value - Namira Azzahra; MF Arrozi Adhikara; Rokiah Kusumapradja (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
RS at Kemayoran continues to experience low conversion of antenatal care (ANC) patients to delivery services, with a conversion rate of 6.9% in 2024. The maternity ward Bed Occupancy Rate (BOR) also remains below national standards. Preliminary assessments indicate dissatisfaction with the hospital’s healthscape, low mimetic desire reflected in limited recommendations, and suboptimal perceived value. This study examines the effects of healthscape and mimetic desire on childbirth location decisions, with perceived value tested as a mediating variable.Methods: A quantitative cross-sectional study was conducted using Structural Equation Modeling (SEM). Data were collected from 210 ANC patients at RSUD Kemayoran through structured questionnaires. Variables included healthscape, mimetic desire, perceived value, and delivery location decision. All instruments met validity and reliability criteria.Results: Healthscape and mimetic desire significantly influenced the decision to choose RSUD Kemayoran for childbirth. Healthscape did not significantly affect perceived value, whereas mimetic desire showed a significant effect. Perceived value had a significant direct effect on delivery decisions but did not mediate the relationships between healthscape or mimetic desire and delivery choice. Healthscape emerged as the most influential determinant.Conclusion: Physical healthcare environments play a critical role in childbirth location decisions. Improving healthscape quality and strengthening professional and social recommendations may enhance ANC-to-delivery conversion rates in public hospitals.